2016
DOI: 10.14260/jemds/2016/1696
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Intestinal Polyps With Clinicopathological Correlation - 2 Years Observational Study at a Tertiary Care Centre of South India

Abstract: BACKGROUNDPolyps of the intestine are common specimens and do not have symptoms unless they cause obstruction or bleed. 1 There are many types of intestinal polyps. Among all polyps, most frequently occurring are adenomatous polyps. Adenomas are considered precursor lesions to invasive carcinoma. Colorectal cancer stands second to lung cancer as the most common cause of cancer mortality. The basic aim of management of patients with adenomatous polyps in the large bowel remains to prevent the development of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…11 The age of the patients ranged from 7 to 84 years with a mean age of 50 years. This finding is in accordance with studies of Chitturi et al 3 and Manakkad et al 7 The age of the patients ranged from 4 to 88 years with a mean age of 46.59 years in study of Chitturi et al 3 Manakkad et al found mean age of 47.14 years with age range of 2-85 years. 7 A lower mean age was observed in studies with larger volume of paediatric patients.…”
Section: Gi Polypoidal Lesionssupporting
confidence: 91%
See 4 more Smart Citations
“…11 The age of the patients ranged from 7 to 84 years with a mean age of 50 years. This finding is in accordance with studies of Chitturi et al 3 and Manakkad et al 7 The age of the patients ranged from 4 to 88 years with a mean age of 46.59 years in study of Chitturi et al 3 Manakkad et al found mean age of 47.14 years with age range of 2-85 years. 7 A lower mean age was observed in studies with larger volume of paediatric patients.…”
Section: Gi Polypoidal Lesionssupporting
confidence: 91%
“…This finding is in accordance with studies of Chitturi et al 3 and Manakkad et al 7 The age of the patients ranged from 4 to 88 years with a mean age of 46.59 years in study of Chitturi et al 3 Manakkad et al found mean age of 47.14 years with age range of 2-85 years. 7 A lower mean age was observed in studies with larger volume of paediatric patients. 11 More than half the cases in our study was noted in 41-60 years age group, comparable to Sharma…”
Section: Gi Polypoidal Lesionssupporting
confidence: 91%
See 3 more Smart Citations